Severe Multiple Sclerosis Relapse After COVID-19 Vaccination: A Case Report - Maniscalco, Giorgia T.; Manzo, Valentino; Di Battista, Maria E.; Salvatore, Simona; Moreggia, Ornella; Scavone, Cristina; Capuano, Annalisa (Frontiers in Neurology, 2021)
We describe a case of acute relapse in a woman with Multiple Sclerosis (MS) shortly after the mRNA COVID-19 vaccination. The patient received a diagnosis of MS in November 2016 at the MS Centre of the A. Cardarelli Hospital (South of Italy). Since that moment, her clinical conditions and pharmacological therapies have been managed at this MS centre where, according to national recommendations, in April 2021, the patient received the BNT162b2 vaccine. Almost 48 h after receiving the vaccine, the patient developed paraesthesia and weakness in her left arm and limbs. The neurological examination revealed walking difficulties while the MRI showed three new voluminous enhancing lesions. After having received methylprednisolone iv for 5 days, the patient's neurological symptoms fully recovered. Along with the implementation of COVID-19 vaccination programmes among vulnerable population, further studies are needed in order to improve our knowledge on the benefit/risk ratio of COVID-19 vaccines.